Power and velocity performance of swing movement in the adolescent male volleyball players - age and positional difference - Junsheng Wang; Zhikai Qin; Zhifeng Wei (BMC, 2024)
Abstract Purpose The performance of swing movement during spikes and serves plays a crucial role in determining the outcomes of volleyball matches. This study aims to explore the effects of the participation of the trunk and lower limbs' involvement on the velocity and power of the swing movement of adolescent male volleyball players, as well as the differences in power and velocity performance of the swing movement among different ages and specific positions. Methods The study involved 22 adolescent male volleyball players, with 11 high school students and 11 middle school students. The Kineo Globus equipment was used to assess the swing movement performance involving different segments, including arm swing movement only involving arm limb participation; upper swing movement involving trunk and arm limb participation; and whole body swing movement involving lower limb, trunk, and arm limb participation. The measured parameters included power and velocity performance levels. Before the test, each subject practiced three movement patterns twice. Results The study found that swing movement involving both the trunk and arm limbs had significantly higher average (F = 17.70, p < 0.001) and peak power performance (F = 31.47, p < 0.001), as well as in average (F = 9.14, p = 0.03) and peak velocity performance (F = 23.17, p < 0.001). There were no significant differences in average (F = 17.70; p = 0.46) and peak power (F = 31.47, p = 0.94), as well as in average (F = 9.14, p = 0.99) and peak velocity performance (F = 23.17, p = 0.90) between movements involving the whole body and those involving the trunk and upper limbs. Among different age groups, the swing movement performance of middle school athletes showed significant enhancements in both average (F = 9.20, p < 0.001) and peak power (F = 19.93, p < 0.001), as well as in average (F = 10.75, p < 0.001) and peak velocity (F = 34.35, p < 0.001) when arm swing with trunk involvement was compared to arm swing movement. High school athletes also showed significant improvements in peak velocity (F = 34.35, p < 0.001), peak power (F = 17.31, p < 0.001), and average power (F = 9.41, p < 0.001) during upper swing movements, except for average velocity performance (F = 1.56, p = 0.21), when compared to arm swing movement. The increase rate in average velocity performance of swing movements involving trunk participation was significantly higher in middle school athletes than in high school athletes (p < 0.001). Among athletes in specific positions, Middle Blocker (MB) players exhibited significantly better average power performance in swing movements involving trunk and arm limb participation compared to Outside Hitter (OH) players (p = 0.04). Furthermore, the rate of average (p = 0.01) and peak (p = 0.03) power change during upper swing movements involving lower limb participation was significantly higher among OH players than MB players. Conclusions The involvement of the trunk segment has been observed to significantly improve power and velocity in swing movements during spike and serves among adolescent male volleyball players. This underscores the importance of coordination between the trunk and arm in influencing swing movement performance during spikes and serves. High school athletes demonstrate superior power and velocity in arm swing movements compared to middle school athletes. MB exhibits greater power in upper limb swing movements than OH, although OH players show better coordination between the arm, trunk, and lower limb segments in the swing movement. To enhance swing movement performance in adolescent male volleyball players, particularly focusing on the trunk segment was crucial. Specialized physical training programs should target improving both arm strength and rotational power of the trunk simultaneously. This approach would help in consistently enhancing coordination between the trunk and arms, ultimately leading to optimized force generation during swing movements such as spikes and serves.